The influence of the addition of tetragonal crystalline titanium oxide nanoparticles on the adhesive and functional properties of layered cementitious composites. (1st February 2020) - Szymanowski, Jacek; Sadowski, Łukasz
Graphical abstract: Abstract: The article presents the results of studies on the effect of tetragonal crystalline titanium oxide (TiO2 ) nanoparticles on the adhesive and functional properties of layered cementitious composites. It was shown that the addition of TiO2 nanoparticles in an amount of 0.5% in relation to the cement mass positively affects the adhesion of the cementitious composite of the overlay to the concrete substrate. This is confirmed by studies carried out with the use of scanning electron microscopy (SEM). The SEM microstructural results confirmed that the improvement of the adhesion is due to the fact that mortar made with the addition of TiO2 nanoparticles in the amount of 0.5% cement mass is characterized by a lower fraction of pores within the interphase. The article also showed that the most favourable results, in terms of higher abrasion resistance, higher subsurface tensile strength and higher hardness of the overlay, were observed for the addition of TiO2 nanoparticles in an amount of 1% in relation to the cement mass.